Assessment of Hand-Arm Vibration in Semi-Mechanized Gardening Activities - Andrade Lima, Roldão Carlos [UNESP]; Soares Rocha, Qüinny [UNESP]; Cazani, Ana Carolina [UNESP]; Guarnetti dos Santos, João Eduardo [UNESP]; Simões, Danilo [UNESP] (Springer Nature, 2022)
Purpose: The objective was to evaluate whether hand-arm vibration acting under workers who perform semi-mechanized activities in the gardening area is in compliance with the precautionary zones. Methods: The collection of vibration data was based on the methodology recommended by the International Organization for Standardization, using a vibration analyzer coupled to a triaxial accelerometer with Integrated Circuit Piezoelectric. Results: When analyzing the values of hand-arm vibration, it was verified that the activities with chainsaw and brush cutter presented acceleration values higher than the exposure limits established by the American Conference of Government Industrial Hygienists. In comparison with the criteria of the International Organization for Standardization—ISO 5349-1, these activities present results of a precautionary zone, indicating the susceptibility to the appearance of white fingers syndrome in at least 3.5 years. Conclusion: The values obtained indicate that occupational exposure to hand-arm vibration in semi-mechanized activities in the gardening area can cause health risks for workers, especially with regard to chainsaw and brush-cutter composite machines. The results show the need for actions that can minimize transmission in activities with a level above the guidelines.
Keywords: Ergonomics; Forest operations; Occupational safety; Physical risks